Tendências e desigualdades da mobilidade urbana no Brasil II: Características e padr\~oes de consumo da mobilidade por aplicativo - Lucas Warwar; Rafael Henrique Moraes Pereira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– Ride-hailing services from companies such as Uber, DiDi and 99 have significantly changed travel behavior in cities across the globe. Despite the common presence of these services in Brazilian cities, there is still little information about who are the users of these services in the country, their sociodemographic characteristics and consumption patterns. This paper presents the first national study on how the use of ride-hailing in Brazil vary by income, race, sex, and age, and highlights spatial differences across metropolitan regions and between central and peripheral urban areas. This study is based on the 2017-2018 Consumer Expenditure Survey carried out by the Brazilian Institute of Geography and Statistics (IBGE), a data source hitherto little used for transportation studies in Brazil. The use of ride-hailing in Brazil is still limited to a small portion of the population. In 2018, only 3,1% of the population above fifteen years old used these services, making an average of 8 trips per month at the average cost of R 22,50 per trip. The results show that the use of ride-hailing in the country is socially and spatially concentrated. The adoption of these services is significantly higher among the population with higher incomes, the young (between 15 and 34 years old), women and the white population. Moreover, approximately 60% of all ride-hailing users in Brazil are concentrated in one of the ten largest metropolitan areas in the country, although adoption rates and average trip frequencies and costs vary considerably across these areas. Finally, we find that the adoption of ride-hailing is higher among the population living in higher density neighborhoods and in large urban centers, with significantly lower adoption in urban peripheral areas and in the countryside. These findings show how the potential benefits of ride-hailing are not evenly distributed, and raise important questions for future policy and research on the effects these services might have for urban mobility patterns.
Keywords: O18; R40; R41; 330; urban mobility; ride-hailing; mobility as a service; Uber; Brazil